2017
DOI: 10.18632/oncotarget.23585
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of LncRNA BCYRN1 promotes tumor progression and enhances EpCAM expression in gastric carcinoma

Abstract: Brain cytoplasmic RNA 1 (BCYRN1), along non-coding RNA, plays a critical role in various diseases, including some cancers. However, the expression of BCYRN1 and its roles in gastric carcinoma (GC) still remain unidentified. Thus, this study employed RT-qPCR to detect expression of BCYRN1 in 85 paired GC samples and adjacent normal tissues, and performed in vitro studies to explore effects of BCYRN1 in GC cells on cell proliferation, apoptosis and migration. We found BCYRN1 was significantly upregulated in GC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…consistent with these results, Hu and lu (12) also reported that BcYrn1 acted as an oncogene in nSclc as evidenced by the high cell proliferation and metastasis induced by BcYrn1. BcYrn1 has been reported to function as an oncogene in colorectal and cervical cancer, as well as in gastric carcinoma (25)(26)(27). Mechanistically, BcYrn1 may regulate gene expression by targeting mirnas.…”
Section: Discussionmentioning
confidence: 99%
“…consistent with these results, Hu and lu (12) also reported that BcYrn1 acted as an oncogene in nSclc as evidenced by the high cell proliferation and metastasis induced by BcYrn1. BcYrn1 has been reported to function as an oncogene in colorectal and cervical cancer, as well as in gastric carcinoma (25)(26)(27). Mechanistically, BcYrn1 may regulate gene expression by targeting mirnas.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that specific lncRNA is closely related to neural cell differentiation, synapses, elevated neuronal excitability, and neural network connection and remodeling, suggesting that it may be involved in the occurrence and development of epilepsy. It is found that in the rat model of epilepsy, the over autophagy and apoptosis of hippocampal neurons can be antagonism by downregulation of lncRNA MALAT1, thus protecting the hippocampus of rats . LncRNA H19 has been reported to promote the apoptosis of hippocampal neurons by inhibiting let‐7b .…”
Section: Discussionmentioning
confidence: 99%
“…It is found that in the rat model of epilepsy, the over autophagy and apoptosis of hippocampal neurons can be antagonism by downregulation of lncRNA MALAT1, thus protecting the hippocampus of rats. 23 LncRNA H19 has been reported to promote the apoptosis of hippocampal neurons by inhibiting let-7b. 24 LncRNA UCA1 inhibits seizures and brain damage caused by epilepsy by modulating the miR-495/Nrf2-ARE signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, recent research indicated that BCYRN1 accelerated the proliferation and metastasis of cervical cancer through regulating miR-138 in vitro and in vivo [9]. And research from Ren et al found that overexpression of BCYRN1 facilitated tumor progression and up-regulated EpCAM expression in gastric carcinoma [10]. Furthermore, BCYRN1 has been illustrated to be greatly expressed in HCC and its expression was actively connected with tumor-node-metastasis and unfavorable prognosis in HCC patients [11].…”
Section: Introductionmentioning
confidence: 99%